Nonandrogenic Anabolic Hormones Predict Risk of Frailty: European Male Ageing Study Prospective Data - Swiecicka A; Lunt M; Ahern T; O'Neill TW; Bartfai G; Casanueva FF; Forti G; Giwercman A; Han TS; Lean MEJ; Pendleton N; Punab M; et al. (OXFORD UNIV PRESS INC, 2022)
Context: Low levels of nonandrogenic anabolic hormones have been linked with frailty, but evidence is conflicting and prospective data are largely lacking.Objective: To determine associations between nonandrogenic anabolic hormones and prospective changes in frailty status.Design/Setting: A 4.3-year prospective observational study of community-dwelling men participating in the European Male Ageing Study.Participants: Men (n = 3369) aged 40 to 79 years from eight European centers.Main Outcome Measures: Frailty status was determined using frailty phenotype (FP; n = 2114) and frailty index (FI; n = 2444).Analysis: Regression models assessed relationships between baseline levels of insulinlike growth factor 1 (IGF-1), its binding protein 3 (IGFBP-3), dehydroepiandrosterone sulfate (DHEA-S), 25-hydroxyvitamin D (25OHD), and parathyroid hormone (PTH), with changes in frailty status (worsening or improving frailty).Results: The risk of worsening FP and FI decreased with 1 standard deviation higher IGF-1, IGFBP-3, and 25OHD in models adjusted for age, body mass index, center, and baseline frailty [IGF-1: odds ratio (OR) for worsening FP, 0.82 (0.73, 0.93), percentage change in FI, -3.7% (-6.0, -1.5); IGFBP-3: 0.84 (0.75, 0.95), -4.2% (-6.4, -2.0); 25OHD: 0.84 (0.75, 0.95); -4.4%, (-6.7, -2.0)]. Relationships between IGF-1 and FI were attenuated after adjusting for IGFBP-3. Higher DHEA-S was associated with a lower risk of worsening FP only in men >70 years old [OR, 0.57 (0.35, 0.92)]. PTH was unrelated to change in frailty status.Conclusions: These longitudinal data confirm the associations between nonandrogenic anabolic hormones and the changes in frailty status. Interventional studies are needed to establish causality and determine therapeutic implications.